THE EFFECT OF DIGITAL MARKETING AND BRAND IMAGE ON PATIENT VISIT DECISIONS AT VWXY HOSPITAL - Galin Mario Bimantara Purba; Endang Sulistyarini; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2026)
This study aims to analyze the influence of digital marketing and brand image on patient visit decisions at a hospital. The background of this study is based on increasing competition among healthcare providers, which requires effective marketing strategies and strong brand positioning. This research uses a quantitative approach with multiple linear regression analysis. The results indicate that digital marketing has a strong and significant effect on patient visit decisions, with a correlation coefficient of 0.884 and regression coefficient of 0.544 (p < 0.001). Brand image also shows a strong influence, with a correlation coefficient of 0.875 and regression coefficient of 1.624 (p < 0.001). Simultaneously, both variables significantly affect visit decisions with an F value of 205.401 and significance of p < 0.001. The coefficient of determination (R²) is 0.820, meaning 82% of the variation in visit decisions is explained by digital marketing and brand image. These findings confirm that digital marketing and brand image are key determinants in influencing patient visit decisions.